QED and the men who made it Dyson, Feynman, Schwinger, and Tomonaga - Schweber, Silvan S. (Hyderabad Universities Press, 1999)
This book covers the development of quantum electrodynamics from its beginning to the present. It is a book full of extraordinary riches, replete with abundantly detailed accounts of the scientific reasoning of the principal contributors, with lengthy quotations from original sources and with a frank but loving presentation of their personalities.
Physics history of science
Keywords: Physicists; Quantum electrodynamics